1999
DOI: 10.1074/jbc.274.14.9160
|View full text |Cite
|
Sign up to set email alerts
|

DNA Contacts Stimulate Catalysis by a Poxvirus Topoisomerase

Abstract: Eukaryotic type 1B topoisomerases act by forming covalent enzyme-DNA intermediates that transiently nick DNA and thereby release DNA supercoils. Here we present a study of the topoisomerase encoded by the pathogenic poxvirus molluscum contagiosum. Our studies of DNA sites favored for catalysis reveal a larger recognition site than the 5-(T/C)CCTT-3 sequence previously identified for poxvirus topoisomerases. Separate assays of initial DNA binding and covalent complex formation revealed that different DNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
(32 reference statements)
1
25
0
Order By: Relevance
“…Available evidence suggests that most of the site specificity is achieved at the level of transesterification chemistry rather than at the noncovalent DNA binding step (24). Whereas the affinity for the target site, the rate of cleavage, and the cleavage equilibrium constant (K cl ) are affected by the nucleotide sequence context surrounding the 5Ј-(C/T)CCTT target site (1,15) in ways that are not well understood in structural terms, the dominant factor triggering the DNA incision reaction is the pentamer 5Ј-CCCTT/3Ј-GGGAA. We have begun to systematically address the features of the individual bases that affect the kinetics of DNA cleavage via position-specific base modifications entailing relatively small additions to, or subtractions from, the standard base structures (11,17), as well as modification by more bulky adducts (16,18).…”
mentioning
confidence: 99%
“…Available evidence suggests that most of the site specificity is achieved at the level of transesterification chemistry rather than at the noncovalent DNA binding step (24). Whereas the affinity for the target site, the rate of cleavage, and the cleavage equilibrium constant (K cl ) are affected by the nucleotide sequence context surrounding the 5Ј-(C/T)CCTT target site (1,15) in ways that are not well understood in structural terms, the dominant factor triggering the DNA incision reaction is the pentamer 5Ј-CCCTT/3Ј-GGGAA. We have begun to systematically address the features of the individual bases that affect the kinetics of DNA cleavage via position-specific base modifications entailing relatively small additions to, or subtractions from, the standard base structures (11,17), as well as modification by more bulky adducts (16,18).…”
mentioning
confidence: 99%
“…Topoisomerases encoded by other genera of poxviruses recognize the same DNA target sequence (6 -10). Available structural and biochemical studies suggest that the assembly of a catalytically competent topoisomerase active site is triggered by recognition of the DNA target (11,12).Early studies using nuclease footprinting, modification interference, modification protection, analog substitution, and UV crosslinking techniques suggested that vaccinia topoisomerase makes contact with several nucleotide bases and the sugar-phosphate backbone of DNA within and immediately flanking the CCCTT element (13)(14)(15)(16)(17)(18)(19). Recent studies have focused on delineating the features of the DNA interface that affect the kinetics of transesterification.…”
mentioning
confidence: 99%
“…Early studies using nuclease footprinting, modification interference, modification protection, analog substitution, and UV crosslinking techniques suggested that vaccinia topoisomerase makes contact with several nucleotide bases and the sugar-phosphate backbone of DNA within and immediately flanking the CCCTT element (13)(14)(15)(16)(17)(18)(19). Recent studies have focused on delineating the features of the DNA interface that affect the kinetics of transesterification.…”
mentioning
confidence: 99%
“…N␦ of Asn-569 is pointed toward the phosphodiester backbone of the scissile strand at a distance of 4.6 Å from the ϩ10 phosphate. A similar scissile strand phosphate contact for Ser-204 of vaccinia topoisomerase is quite plausible given that (i) the footprint of the vaccinia protein on DNA extends 13 bp 5Ј of the cleavage site (9, 41), (ii) both noncovalent and covalent binding of vaccinia topoisomerase to CCCTT-containing DNA are reduced significantly when there are fewer than 10 bp on the 5Ј-side of the cleavage site (42), and (iii) the rate of DNA cleavage is affected by alterations of the ϩ9 and ϩ10 base pairs in the major groove (43).…”
Section: Mutagenesis Strategy and Production Of Mutant Proteins-mentioning
confidence: 99%